Management of the adverse events of afatinib: a consensus of the recommendations of the Spanish expert panel. (January 2015) - Arriola, Edurne; Reguart, Noemi; Artal, Angel; Cobo, Manuel; García-Campelo, Rosario; Esteban, Emilio; Rodríguez, Mari Carmen; García-Muret, Maria Pilar
ABSTRACT : Afatinib is an irreversible ErbB family blocker tyrosine kinase inhibitor (TKI), which has recently been approved for the treatment of patients with EGFR M+ non-small cell lung cancer. As observed with reversible EGFR TKIs, it can induce class-effect adverse events. Appropriate management of afatinib-related adverse events improves quality of life and clinical outcomes in these patients. Here we provide practical recommendations for the prophylaxis and treatment of the most common of these (e.g., diarrhea, rash, mucositis and others).